Pengaruh Pertumbuhan Perusahaan, Leverage, Dan Audit Tenure Terhadap Audit Delay - Sari, Selvia Eka; Sasana, Lodang Prananta Widya (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This research aims to empirically prove the influence of company growth, leverage, and audit tenure on audit delay. This research was conducted in manufacturing companies in the property and real estate sector. The research method used is quantitative. The type of data used is secondary data in the form of annual financial statements published on the Indonesia Stock Exchange (BEI) for the years 2019-2023. The sample was collected using the purposive sampling method. The number of companies sampled for the research was 22 companies over a 5-year period, resulting in a total of 110 observation data points. The results of the F statistical test show that company growth, leverage, and audit tenure simultaneously affect audit delay. The results of the t-statistic test for the company growth variable partially do not affect audit delay, whereas leverage partially affects audit delay, and audit tenure also partially affects audit delay.